KANDUNGAN SENYAWA BIOAKTIF DAN AKTIVITAS ANTIOKSIDAN BAWANG MERAH NGANJUK (Allium Cepa L.) - Shela Insanul Hikmah; Mirwa Adiprahara Anggarani (Unesa Journal of Chemistry, 2021)
Nganjuk, East Java is a shallot producing area, but its potential as a medicinal and cosmetic plant has not been developed much, especially in the use of its bioactive compounds. The content of bioactive compounds is considered to be potential as antioxidants. This study aimed to determine bioactive compounds and antioxidant activity. Extraction of the samples used a multilevel maceration method with three types of solvents according to polarity, namely ethanol (polar), ethyl acetate (semi-polar), and dichloromethane (non-polar). The type of sample testing carried out is the measurement of bioactive compounds analysis and determination of antioxidant activity using the DPPH method. Flavonoid levels used the AlCl3 method and for the determination of phenolic levels using the Folin Ciocalteu method. The results showed that Nganjuk shallot extract contained bioactive compounds of alkaloids, flavonoids, phenolics, saponins, tannins, triterpenoids, and quinones. The total flavonoid and phenolic levels were weak, namely 0,881% respectively, and 0,966%. Antioxidant activity is shown at the IC50 values ​​of in the ethanol, ethyl acetate, and dichloromethane extracts were 384,0341 ppm; 5336,7889 ppm; 884,2754 ppm. These results indicate that the antioxidant activity of Nganjuk activity is very weak because the value of IC50 > 200 ppm. Key words: nganjuk shallot, bioactive compounds, antioxidant activity